ACADEMIC RESILIENCE AMONG INDONESIAN TRAINEE TEACHERS: A COMPARATIVE STUDY OF GENDER, YEAR OF STUDY, AND ACADEMIC ACHIEVEMENT - Milla, Sri Nurul; Faizuddin, Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Teachers well-being and effectiveness are essentials for sustainable future of education. Moreover, teachers need to be academically resilient. This study aims to examine the level of academic resilience among Indonesian trainee teachers and its differences by gender, and year of study, and academic achievement. Consisting of 30 items, The Academic Resilience Scale developed by Cassidy (2016) was distributed to 300 Indonesian trainee teachers coming from various national universities. The data showed that Indonesian trainee teachers have a high level of academic resilience. There were no significant gender differences in the resilience score. Furthermore, the Pearson Product Moment test indicated that academic resilience was found to be positively correlated to their academic performance yet the correlation was not significant (R=0,086, sig >0.05). Conversely, academic resilience was negatively and significantly correlated to students’ year of study (R=-0.151, sig <0.05). This concerning pattern underscores the need to targeted interventions to enhance academic resilience, particularly among senior students.